A study to determine the association between tobacco smoking habit and oral candidal infection in median rhomboid glossitis by cytologic and histopathologic methods - Anitha Bojan; Winnifred Christy; Kaleel Kurian; S Elangovan (Wolters Kluwer Medknow Publications, 2012)
Objectives: To determine the association, if any, between tobacco smoking and candidal infection in median rhomboid glossitis (MRG) and to histopathologically evaluate the presence of dysplastic changes in it. Study design: Hospital-based study consisting of 100 subjects who satisfied the clinical criteria of MRG- Smears and swabs were collected to ascertain the presence of Candida and sub-typing was done utilizing the CHROMagar technique. Biopsy and histopathological examination was done to determine the presence or absence of dysplasia of the lesional tissue. Results: All the subjects were male and had the habit of smoking- Smears and swabs taken from glossal lesion of 60 subjects' showed 100% candidal positivity. Tissue section from 31 subjects showed histological picture consistent with MRG and 23 (74%) showed dysplastic changes. Conclusion: MRG is a Candida-associated lesion and the tobacco-smoking habit in our cohort may play an important role in increasing the candidal colonization. As some of our cases exhibited mild epithelial dysplasia, both candidal colonization and smoking habits may have contributed to the dysplastic changes.